Mixed Periampullary Adenocarcinoma and Somatostatinoma with Small Bowel Gastrointestinal Stromal Tumour in Neurofibromatosis Type 1 - Tewari, Nilanjana; Rollins, Katie; Gandhi, Nirav; Kaye, Phillip; Lobo, Dileep N (JOP. Journal of the Pancreas, 2014)
Context Gastrointestinal (GI) involvement is present in about one quarter of cases of neurofibromatosis type 1 (NF1). Adenocarcinomas have been reported in several organs. Gastrointestinal stromal tumors are the most common GI lesion seen in NFI. GISTs in combination with ampullary neuroendocrine tumors in NF-1 have been reported rarely. Case report We present the case of a 44-year-old man who presented with a history of obstructive jaundice and weight loss. Investigations revealed a pancreatic tumor associated with a common bile duct (CBD) stricture. At operation, an ampullary adenocarcinoma that infiltrated into the head of pancreas with an adjacent somatostatinoma was found. In addition, a small bowel GIST was present. Conclusions Mixed periampullary adenocarcinoma and somatostatinoma in a patient with NF1 has only been previously reported once. The current case highlights the spectrum of associated tumor types which can be seen in association with NF1. Patients with NF1 who present with jaundice and weight loss should be investigated in the usual manner with increased suspicion for duodenal and ampullary tumors. Image: MRCP demonstrating significant intra-hepatic biliary duct dilatation.